PENYULUHAN DAN EDUKASI TENTANG KOMUNIKASI YANG BAIK ANTAR SESAMA DI SEKOLAH DASAR INPRES MOUTONG TIMUR - Fatma L. Rahim; Tri Setiawati Maulana (Journal of Hulonthalo Service Society (JHSS), 2025)
This community service activity was carried out in Salepae Village, Moutong District, Parigi Moutong Regency, Central Sulawesi Province. This outreach and education activity regarding good communication between residents was carried out on Saturday 17 July 2023 at the East Moutong Inpres Elementary School, Salepae Village, accompanied by the class VI homeroom teacher. Grade VI students do not fully understand the importance of using polite language and tone when communicating with others. The purpose of community service activities, especially among children, is to increase children's awareness of the importance of using polite language and tone when communicating with others. as an alternative to meet basic needs in communication. The implementation method used in community service activities, especially for class VI students of SD Inpres Putong Timur, Salepae Village, namely: 1) problem identification; 2) forming a team of proposers; 3) observation of activity locations; 4) data collection; 5) identification of activity participants; 6) preparation of supporting materials, facilities and infrastructure; 7) delivery of materials; 8) development of local resources; 9) documentation; 10) reporting; and 11) publication. The results of community service, especially for class VI students at SD Inpres Putong Timur, Salepae Village really understand the importance of speaking or communicating using good Indonesian and a tone of voice that is pleasant to hear by others.